Pendampingan Sadar Wisata dan Pembuatan Jalur Interpretasi Wisata Trekking di Desa Sirnajaya melalui Program MBKM Membangun Desa Wisata - Maesa Quratuain; Revi Agustin Aisyianita; Amelia Dwi Juliana (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
This paper discusses the implementation of the MBKM (Community Development through Student Community Service) program in Sirnajaya Village, Bogor Regency, West Java, Indonesia. The program focuses on raising awareness among the local community about responsible tourism practices and creating a trekking interpretive trail. The concept of "Desa Wisata" (Village Tourism) is emphasized, which involves active participation from the local community and utilizes local resources and wisdom to enhance the village's economy and well-being. The uniqueness of Sirnajaya Village, with its pristine natural beauty and limited mass tourism, is considered an attractive factor. The growing interest in nature-based tourism, especially in the context of the new normal and the preference for activities such as trekking, further supports the development of trekking tourism in the village. The importance of interpretive trails in connecting visitors with the natural resources is emphasized, as it enhances visitors' experiences and promotes conservation. The program involves the participation of D4 Tourism students from Jakarta State University and the local community, utilizing the Participatory Rural Appraisal (PRA) approach. The preparation phase includes site selection, task assignment, and field visits. Benchmark analysis is conducted by studying similar programs, with the Sentul area as a reference. The final phase focuses on socializing and developing the trekking interpretive trail through workshops, lectures, and expert discussions. The program aims to make Sirnajaya Village a sustainable tourism destination, benefiting both the local community and tourists.